The Roles of Liver-Resident Lymphocytes in Liver Diseases - Wang, Yanan; Zhang, Cai (Frontiers in Immunology, 2019)
Tissue-resident lymphocytes usually reside in barrier sites and are involved in innate and adaptive immunity. In recent years, many studies have shown that multiple types of lymphocytes are resident in the liver, including memory CD8+ T (TRM) cells; “unconventional” T cells, such as invariant natural killer T (iNKT) cells, mucosal associated invariant T (MAIT) cells, and γδT cells; innate lymphoid cells (ILCs) such as natural killer (NK) cells and other ILCs. Although diverse types of tissue-resident lymphocytes share similar phenotypes, functional properties, and transcriptional regulation, the unique microenvironment of the liver can reshape their phenotypic and functional characteristics. Liver-resident lymphocytes serve as sentinels and perform immunosurveillance in response to infection and non-infectious insults, and are involved in the maintenance of liver homeostasis. Under the pathological conditions, distinct liver-resident lymphocytes exert protective or pathological effects in the process of various liver diseases. In this review, we highlight the unique properties of liver-resident lymphocytes, and discuss their functional characteristics in different liver diseases.